Convergence and gaps between medical courses educational projects and the National Curriculum Guidelines: university professors' perceptions - Oliveira, Carlos Alberto de; Amaral, Eliana Martorano; Cyrino, Eliana Goldfarb [UNESP]; Gianini, Reinaldo Jose (Univ Estadual Paulista-unesp, 2021)
To understand the National Curriculum Guidelines (NCG) it is ne cessary to contextualize the reality of each educational institution. The effective implementation of the guidelines requires the (re)orientation of the health e ducation process; promoting integration between the course educational project (CEP); Brazilian National Health System (SUS) and professor engagement. We conducted a qualitative exploratory study using questionnaires to capture professors' perceptions of the alignment between medicine CEPs and the NCG. Content analysis was performed to develop thematic categories. The professors at one school acknowledged that the CEP and NCG were not aligned and their responses revealed that teaching is determined by each professor's professional and personal background. In another school whose curriculum reform adopted active teaching-learning methodologies, the professors felt a sense of ownership in relation to the NCG. We therefore conclude that the CEP change process requires time, dedication and effective communication or, in other words, greater change within the education institution.
Keywords: Medical education; Teaching-service integration; Health planning guidelines